D. 300 it is. is there more?
<span>
<span><span>
x
y=2*(0.5)^x
</span><span>-10
2048
</span>
<span>
-9
1024
</span>
<span>
-8
512
</span>
<span>
-7
256
</span>
<span>
-6
128
</span>
<span>
-5
64
</span>
<span>
-4
32
</span>
<span>
-3
16
</span><span>-2
8
</span>
<span>
-1
4
</span>
<span>
0
2
</span>
<span>
1
1
</span>
<span>
2
0.5
</span>
<span>
3
0.25
</span>
<span>
4
0.125
</span>
<span>
5
0.0625
</span>
<span>
6
0.03125
</span>
<span>
7
0.015625
</span>
<span>
8
0.0078125
</span>
<span>
9
0.00390625
</span>
<span>
10
0.00195313
As x goes to negative infinity the function grows to infinity.
As x grows to infinity the function decreases an approximate to zero. </span></span></span>
Ok so the first step is to -1 from both sides. On the right side it cancels out and on the left side it = -16. So now your left with -16= 8x. Your still not done yet though. So now what you want to do is divide both sides by 8. On the right side it cancels out and you bring down x and on the left side it equals -2. So x=-2. So to verify it you have to plu -2 back into the equation. So -15= 8 Times -2 +1 so 8 Times -2 = -16 plus one is -15. Hoped that helped!!
A=3X-3
B=-X+3
If A+B=2X-2, then using equalivant exchange A=2X-2-B and
B=2X-2-A
If A-B=4X-8, then A=4X-8+B and -B=4X-8-A(or B=-4X+8+A)
Since A equals both 2x-2-B and 4X-8+B we can add both equations to equal 2A=6X-6 now we devide that by 2 to get
A=3X-3
Do the exact same for B, so b equals both 2X-2-A and -4X+8+A
We can add them both to get 2B=-2X+6 and decide that by 2 to get B=-X+3
Answer:
7
Step-by-step explanation:
[(1/3 – 1/9)² + (1/3)³] : (1/3)⁴
Next, we shall simplify (1/3 – 1/9)². This is illustrated below:
(1/3 – 1/9)² = ((3 – 1)/9)² = (2/9)²
[(1/3 – 1/9)² + (1/3)³] : (1/3)⁴
= [(2/9)² + (1/3)³] : (1/3)⁴
= [4/81 + 1/27] : 1/81
= [(4 + 3)/81 ] : 1/81
= 7/81 : 1/81
= 7/81 ÷ 1/81
Invert
= 7/81 × 81/1
= 7